2019
DOI: 10.1080/02640414.2019.1585313
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit attitudes towards sport among young elite athletes with high versus low burnout symptoms

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…To sum up, the present study revealed that former agonist road cyclists still involved in cycling (either in a different specialty or with a different role) reported that they had experienced lower levels of emotional and physical exhaustion and sport devaluation during the last year practicing this specialty, with respect to both those who started practicing a different sport and those who definitively abandoned it. Interestingly, the presence of differences in these two burnout components, as well as the absence of differences in reduced sense of accomplishment, is coherent with a recent study by Gerber et al (2019), which highlighted greater emotional/physical exhaustion and sport devaluation in young elite athletes reporting high compared to low burnout symptoms. A reasonable explanation for the results observed in our study is that some differences in burnout levels actually existed (contributing to the decision of remaining in cycling or not), and these differences have been magnified by the subsequent experiences of participants.…”
Section: Discussionsupporting
confidence: 86%
“…To sum up, the present study revealed that former agonist road cyclists still involved in cycling (either in a different specialty or with a different role) reported that they had experienced lower levels of emotional and physical exhaustion and sport devaluation during the last year practicing this specialty, with respect to both those who started practicing a different sport and those who definitively abandoned it. Interestingly, the presence of differences in these two burnout components, as well as the absence of differences in reduced sense of accomplishment, is coherent with a recent study by Gerber et al (2019), which highlighted greater emotional/physical exhaustion and sport devaluation in young elite athletes reporting high compared to low burnout symptoms. A reasonable explanation for the results observed in our study is that some differences in burnout levels actually existed (contributing to the decision of remaining in cycling or not), and these differences have been magnified by the subsequent experiences of participants.…”
Section: Discussionsupporting
confidence: 86%
“…A total of 180 studies were subsequently omitted, leaving 8 studies eligible for the final analysis. 1,6,9,11,12,16,21,23 Details of the study selection process are presented in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Although all of the studies included in this systematic review used athlete burnout as the outcome of measure, only 3 (37.5%) of the included studies compared ABQ results directly with specialization status of the athletes. 16,21,23 Other comparisons with athlete burnout included feelings of emotion, such as fear of failure, 9 perceived stress, 9 implicit attitude toward sport, 6 self-acceptance, 11 and enjoyment, 23 as well as personality traits, such as perfectionism 1,11 and intrinsic motivation. 1,21…”
Section: Resultsmentioning
confidence: 99%
“…Burnout in the field of physical activity and sport is considered a state that may be associated with negative variables such as the abandonment of physical practice, decreased physical performance, poor enjoyment of the sport activity practiced or increased injuries [ 28 ]. Athletes with high levels of burnout often develop behaviors that distance them from sport, explicitly manifesting a separation from physical practice [ 29 ]. Various researchers have observed that, in situations of sports stress, athletes with greater mental toughness have a greater ability to protect themselves against its adverse effects, developing fewer health problems and less burnout [ 30 ].…”
Section: Introductionmentioning
confidence: 99%